Economic Development as Opportunity Equalization - Roemer, John E. (Oxford University Press on behalf of the World Bank, 2015)
Economic development should be conceived of as the degree to which an economy has implemented an efficient and just distribution of economic resources. The ubiquitous measure of GDP per capita reflects a utilitarian conception of justice, where individual utility is defined as personal income, and social welfare is the average of utilities in a population. A more attractive conception of justice is opportunity-equalization. Here, a two-dimensional measure of economic development is proposed, based upon viewing individuals’ incomes as a consequence of circumstances, effort, and policy. The first dimension is the average income level of those in the society with the most disadvantaged circumstances, and the second dimension is the degree to which total income inequality is due to differential effort, as opposed to differential circumstances. This pair of numbers is computed for a set of 22 European countries. No country dominates all others on both dimensions. The two-dimensional measure induces a partial ordering of countries with respect to development.